The Influence of Asset Structure, Business Risk, Profitability, Company Size, and Capital Structure on Company Value in Property and Real Estate Companies Listed on the Indonesia Stock Exchange (IDX) for the 2015 – 2019 Period - Robin, Robin; Bertuah, Eka (Budapest International Research and Critics University, 2021)
At the national level, the property industry has a considerable influence. The rapid growth of the property industry will have an impact on other industries. Examples include the material, logistics and service industries, as well as the banking industry through KPR (House Ownership Credit) which will have an impact on job creation and the economy. growth in the country. This study aims to determine the effect of Asset Structure, Business Risk, Profitability, Company Size and Capital Structure on Firm Value (PBV). The period of this research is 5 (five) years, namely 2015 to 2019. This study uses panel data regression analysis. The population of this study includes property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the period 2015 – 2019. The results of this study indicate that the asset structure, business risk, profitability, firm size and capital structure have a simultaneous effect on firm value. Profitability and Capital Structure variables have a positive and significant effect on firm value. Asset structure, business risk, and firm size have no effect on firm value. This study contributes to testing and proving signaling theory and firm value on profitability and capital structure that affect firm value. and the size of the company has no effect on the value of the company. This study contributes to testing and proving signaling theory and firm value on profitability and capital structure that affect firm value. and the size of the company has no effect on the value of the company. This study contributes to testing and proving signaling theory and firm value on profitability and capital structure that affect firm value.